Comparison of molecular and MALDI-TOF MS identification and antifungal susceptibility of clinical Fusarium isolates in Southern China - Guo, Penghao; Chen, Jianlong; Tan, Yiwei; Xia, Li; Zhang, Weizheng; Li, Xiaojie; Jiang, Yujie; Li, Ruiying; Chen, Chunmei; Liao, Kang; Peng, Yaqin (Frontiers in Microbiology, 2022)
Background Fusarium species are opportunistic causative agents of superficial and disseminated human infections. Fast and accurate identification and targeted antifungal therapy give help to improve the patients’ prognosis. Objectives This study aimed to evaluate the effectiveness of matrix-assisted laser desorption ionisation time of flight mass spectrometry (MALDI-TOF MS) for Fusarium identification, and investigate the epidemiology and antifungal susceptibility profiles of clinical Fusarium isolates in Southern China. Methods There were 95 clinical Fusarium isolates identified by DNA sequencing of translation elongation factor 1-alpha (TEF1α) and MALDI-TOF MS, respectively. Antifungal susceptibility testing of isolates was performed by broth microdilution according to the CLSI approved standard M38-A3 document. Results Seven species complexes (SC) with 17 Fusarium species were identified. The most prevalent SC was the F. solani SC (70.5%, 67/95), followed by the F. fujikuroi SC (16.8%, 16/95). F. keratoplasticum within the F. solani SC was the most prevalent species (32.6%, 31/95). There were 91.6% (87/95) of isolates identified by MALDI-TOF MS at the SC level. In most of species, amphotericin B and voriconazole showed lower MICs compared to itraconazole and terbinafine. The F. solani SC showed higher MICs to these antifungal agents compared to the other SCs. There were 10.5% (10/95) of strains with high MICs for amphotericin B (≥8 μg/ml), terbinafine (≥32 μg/ml) and itraconazole (≥32 μg/ml) simultaneously, mostly focusing on F. keratoplasticum (9/10). Conclusion MALDI-TOF MS exhibited good performance on the identification of Fusarium strains at the SC level. The F. solani SC was the most prevalent clinical SC in Southern China. The MICs varied significantly among different species or SCs to different antifungal agents.